Occurrence of Listeria species in prepacked retail sandwiches. - Wilson, I. G. (Cambridge University Press, 1996)
A survey of 725 prepacked sandwiches was conducted examining for the presence on enrichment, and by plate count, of Listeria species. Sandwiches were found to contain Listeria sp. more frequently than their component foods. Chicken, beef and bacon fillings were associated with more frequent isolation. Salad also was associated with more frequent isolation, but the increase was not significant. On enrichment, over 15% of sandwiches contained Listeria species. L. innocua and L. monocytogenes were the only species isolated by plate count at numbers > or = 100 cfu/g (1.5% of total samples). Potentially hazardous levels of L. monocytogenes (defined as > or = 10(3) cfu/g) were found in two sandwiches examined (0.3%), indicating that although Total Viable Counts (TVCs) may often be high, the risk of listeriosis to vulnerable individuals from sandwiches is relatively low. It is important to distinguish the risk of consuming potentially hazardous levels of a pathogen in food from the risk of contracting illness as a result of such an event.